2016
DOI: 10.1002/jhm.2551
|View full text |Cite
|
Sign up to set email alerts
|

Pleural fluid procalcitonin to distinguish infectious from noninfectious etiologies of pleural effusions

Abstract: In this study we investigate the diagnostic value of pleural fluid procalcitonin (PCT) in distinguishing infectious and noninfectious etiologies of pleural effusion. We reviewed the medical records of 75 hospitalized patients who underwent thoracentesis between 2011 and 2012. Data on pleural fluid lactate dehydrogenase (LDH), protein, albumin, cell count and differential, pH, Gram stain and culture, cytology, triglyceride, cholesterol, amylase, and PCT were collected. Data on serum LDH, protein, albumin, proth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Escalation of PCT is now regarded as a useful serological biomarker of bacterial infection (8). In recent years, some multi-center clinical studies have explored the diagnostic effectiveness of PCT in serum or PE, but have drawn conflicting conclusions, leading to a controversial status for the diagnostic role of pleural PCT (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Escalation of PCT is now regarded as a useful serological biomarker of bacterial infection (8). In recent years, some multi-center clinical studies have explored the diagnostic effectiveness of PCT in serum or PE, but have drawn conflicting conclusions, leading to a controversial status for the diagnostic role of pleural PCT (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Khosla, et al investigated the diagnostic value of PCT in distinguishing infectious and noninfectious etiologies of pleural effusion, and the analysis results showed that PCT is a novel biomarker for diagnosing infectious pleural effusion [14]. Facing with these contradictory outcomes, here we examined the relationship between p-PCT and s-PCT levels in EPE from different groups and explored the various causes of pleural effusions.…”
Section: Discussionmentioning
confidence: 94%
“…LDH is an acute reactant associated with the degree of inflammation in infectious pleural effusions; however, it is also elevated in malignant pleural effusions as LDH also acts as an intracellular enzyme that indicates the degree of cell turnover within the pleural space 1 . In addition, several studies have explored the potential utility of other new biomarkers of infection (e.g., C-reactive protein 17 , procalcitonin 18 , 19 , presepsin 20 , cell-free DNA 21 , Interleukin-27 22 ) to diagnose infectious pleural effusion. A prior study reported 75 patients with significantly elevated pleural fluid procalcitonin in IPEs (empyemas and PPEs) and pleural fluid procalcitonin > 0.25 ng/ml had a sensitivity of 77.78% and specificity of 74.14% for the diagnosis of IPEs 19 .…”
Section: Discussionmentioning
confidence: 99%